Theoretical Foundations of Bricolage, Stakeholder Synergy and Effectuation: Towards the Conceptualization of Dynamic Capabilities - Magdalena DOMINICZEWSKA (Communications of International Proceedings, 2021)
This paper provides a critical literature review on the dynamic capabilities key components which are bricolage, stakeholder synergy and effectuation. The aim of this paper is to prepare theoretical foundations for further empirical work on the concept of dynamic capabilities, so the consolidation of the concept, defining proper assumptions, variables, and relationships to be considered and further building solid and comprehensive scale for measuring the enterprise dynamic capabilities.
Keywords: Dynamic Capabilities; Bricolage; Stakeholder Synergy; Effectuation.